The non-profit sector in the framework of the new technological age: the challenge of social Crowdfunding in Spain. analysis of the case of the asociation Alba Pérez, fight against childhood cancer - Sajardo Moreno, Antonia; Gil Ibáñez, Marta; Pérez Sempere, Salvador (REVESCO. Revista de Estudios Cooperativos, 2017)
The dawn of the 21st century is presented to economies and societies within the framework of a challenging double paradigm shift. One, encouraged by the ruling neoliberalism in much of the advanced world, has caused society itself to admit the responsibility of the governing structures in the provision of the services that make up the welfare state. Another, technological, that has changed the way society is informed, communicates and relates. Faced with these two realities, civil society has become aware of its transforming role and impelling changes, as well as the growing needs for social care that have emerged at this beginning of the century, the essential to meet them and of course, their need for funding . It is in this area that the application of communication and marketing strategies based on the new technological reality takes on a special relevance in the search for alternative solutions that give viability to concrete projects. In this article, we analyze the case of the Alba Pérez Association for the fight against childhood cancer, and its use of the social tools provided by the Internet to build and revitalize a community, the alberos, committed to the cause that Defends the Association and ready to provide resources for the achievement of its objective. In this context, we will analyze the operational dynamics of crowdfunding, marketing and communication tools, as well as their success factors. The objective of this work is to offer an example of good practices in the development of successful fundraising techniques, such as crowdfunding, which allows the Non Profit Sector to draw according to its reality, resources and objectives dethroning the myth of absolute necessity Of public financing, in the fulfillment of its mission.
Keywords: Sharing Non-Profit Sector; technology; crowdfunding; fundraising; marketing; social networks